KEBERLANJUTAN NILAI PROGRAM PERBAIKAN KAMPUNG SANGKRAH KOTA SURAKARTA - , JAYANTI ARUM NUGRAHAENI, Prof. Ir. Sudaryono, M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Kampung Sangkrah was an informal slum settlement which now becomes well arranged and legal urban kampung. The change in Kampung Sangkrah was started since the latest time of 1970s, after the kampung upgrading program existed. Up to this time, the kampung upgrading program still gives beneficial things to the society. The previous statement encourages a continuing research about the existence of program value in Kampung Sangkrah with the objective of valuating the kampung upgrading program conceptually towards its development and impact. The research is conducted using qualitative inductive method with phenomenology approach. The result of the research is a concept of the continuity value of kampung upgrading program. The continuity of program value here means the existence of using the outcome program (program value) and changing encouragement. Those two things become important factors which influence the development of all aspects in Kampung Sangkrah until now on.